Implementation Of Speech Therapy Services And Assessment Of Speech Disorders In Regional Pedagogical-Psychological Support Centers - Hovyan, Gohar; Harutyunyan, Elen; Papoyan, Zhenya; Kosyan, Laura; Margaryan, Ani
The analysis of scientific-methodological literature, familiarization with the work experience of specialists from pedagogical-psychological support centers and public school teachers, as well as the study of the decisions of the Government of the Republic of Armenia regarding the assessment criteria and tools of an individual's functionality, indicate that the issues of speech therapy assessment for children with speech disorders, based on the WHO International Classification of Functioning, Disability, and Health (ICF), are underdeveloped. The Government of Armenia's 2003 Decision No. 780-N on "Medical-Social Examination Criteria" is often outdated. As of February 1, 2023, evaluations for individuals applying for medical-social examinations but not yet assessed are conducted according to the updated criteria set by this decision (Republic of Armenia, 2023). The formation of a high-quality education system for children with special educational needs in Armenia and the challenges in implementing speech therapy assessments can be attributed to insufficient research and development in this area. Based on recent legislative changes, regional pedagogical-psychological support centers are responsible for evaluating children's special educational needs, providing relevant conclusions regarding their educational organization, offering support services, conducting consultations and training for teachers, and implementing other functions outlined by law.
Keywords: Pedagogy; Psychology